2001
DOI: 10.1007/bf03016588
|View full text |Cite
|
Sign up to set email alerts
|

In rabbits, landiolol, a new ultra-short-acting β-blocker, exerts a more potent negative chronotropic effect and less effect on blood pressure than esmolol

Abstract: P Pu ur rp po os se e: : To compare the cardiovascular and sympathetic effects of a new ultra-short-acting, highly cardioselective ß-blocker, landiolol, with esmolol, using an in vivo rabbit model. ) were given intravenously, and the effects on heart rate (HR) mean arterial pressure (MAP) and renal sympathetic nerve activity (RSNA) were compared.R Re es su ul lt ts s: : Both landiolol and esmolol produced a dose-dependent decrease in HR. The maximum percent reductions of HR were similar with landiolol 3 mg·kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
83
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 13 publications
6
83
0
Order By: Relevance
“…1,2 We and others have documented its efficacy as a ß-adrenergic receptor antagonist, when administered as an iv bolus.3,4 Here, we show that an elderly patient with paroxysmal atrial tachycardia was successfully treated with bolus landiolol iv.An 84-yr-old male patient (161 cm, 68 kg) was scheduled for repair of a right femoral fracture under spinal anesthesia. His preoperative electrocardiogram showed a complete right bundle-branch block, and he had a history of palpitations.…”
supporting
confidence: 49%
“…1,2 We and others have documented its efficacy as a ß-adrenergic receptor antagonist, when administered as an iv bolus.3,4 Here, we show that an elderly patient with paroxysmal atrial tachycardia was successfully treated with bolus landiolol iv.An 84-yr-old male patient (161 cm, 68 kg) was scheduled for repair of a right femoral fracture under spinal anesthesia. His preoperative electrocardiogram showed a complete right bundle-branch block, and he had a history of palpitations.…”
supporting
confidence: 49%
“…Although landiolol is reported to be more potent than esmolol as a ß-blocker, 1,2 it is also reported that the cardiodepressant effect of landiolol is less than that of esmolol. 3 It is most likely that differences in pre-ischemic hemodynamics lead to differences in postischemic recovery. We chose the doses of ß blockers based on their cardiodepressant effects instead of their ß1-adrenoceptor blocking potency.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although this agent is more potent than esmolol as a ß-antagonist, 1,2 the cardiodepressant effect of landiolol is less than that of esmolol. 3 In addition, it has a short duration (half-life of four minutes) of activity, enabling rapid recovery after cessation of administration by rapid hydrolysis of its ester link. 1 It has neither intrinsic sympathomimetic activity nor significant membrane-stabilizing activity.…”
mentioning
confidence: 99%
“…7,8 While landiolol is more potent than esmolol 7 in terms of chronotropy, it also has less effects on blood pressure than esmolol in anesthetized rabbits. 9 Although there have been great advances in cardiac surgical techniques in the past decade, postoperative support with inotropic agents is still frequently necessary. 10 Further, intraoperative prevention of hypotension and arrhythmias and maintenance of cardiac output (CO) are critical in terms of patient outcome.…”
Section: Contexte : L'usage Clinique De Fortes Doses Thérapeutiques Dmentioning
confidence: 99%
“…Sasao et al 9 demonstrated that 300 µg·kg -1 ·min -1 esmolol produced hypotension in rabbits, while 300 µg·kg -1 ·min -1 landiolol had no effect on blood pressure. In our study, 1000 µg·kg -1 ·min -1 landiolol produced a 20% decrease in SBP from baseline value.…”
Section: Me Et Th Ho Od Ds Smentioning
confidence: 99%